HOSPITAL MERGERS AND ANTITRUST IMMUNITY: THE ACQUISITION OF PALMYRA MEDICAL CENTER BY PHOEBE PUTNEY HEALTH. (4th December 2018) - Garmon, Christopher; Kmitch, Laura
Abstract: On December 15, 2011, Phoebe Putney Health acquired the only other hospital in Albany, Georgia—Palmyra Medical Center—despite the Federal Trade Commission's challenge of the merger as anticompetitive. The acquisition was consummated after the district and appellate courts ruled that Phoebe Putney had antitrust immunity due to its regulation by the local Hospital Authority of Albany-Dougherty County. In February 2013, the Supreme Court reversed these rulings and remanded the case back to the lower courts, after Palmyra Medical Center had become part of Phoebe Putney Memorial Hospital, making a divestiture infeasible. The acquisition of Palmyra Medical Center by Phoebe Putney provides an opportunity to study the effects of an otherwise anticompetitive hospital merger subject to local regulation. We found that, after a large price spike in the first post-merger year, the commercial price of inpatient hospital services in Albany, Georgia, moderated toward the control group price in subsequent post-merger years. Regarding quality, we found a significant post-merger reduction in inpatient hospital quality relative to controls across many quality metrics. We discuss the implications of these findings for recent initiatives that grant hospitals antitrust immunity in exchange for local regulation.